Potential of Pichia pastoris for the production of industrial penicillin G acylase - Marešová, Helena; Palyzová, Andrea; Plačková, Martina; Grulich, Michal; Rajasekar, Vyasa Williams; Štěpánek, Václav; Kyslíková, Eva; Kyslík, Pavel (Folia microbiologica, 2017)
This study deals with the potential of Pichia pastoris X-33 for the production of penicillin G acylase (PGAA) from Achromobacter sp. CCM 4824. Synthetic gene matching the codon usage of P. pastoris was designed for intracellular and secretion-based production strategies and cloned into vectors pPICZ and pPICZα under the control of AOX1 promoter. The simple method was developed to screen Pichia transformants with the intracellularly produced enzyme. The positive correlation between acylase production and pga gene dosage for both expression systems was demonstrated in small scale experiments. In fed-batch bioreactor cultures of X-33/PENS2, an extracellular expression system, total PGAA expressed from five copies reached 14,880 U/L of an active enzyme after 142 h; however, 60% of this amount retained in the cytosol. The maximum PGAA production of 31,000 U/L was achieved intracellularly from nine integrated gene copies of X-33/PINS2 after 90 h under methanol induction. The results indicate that in both expression systems the production level of PGAA is similar but there is a limitation in secretion efficiency.
Keywords: Gene Dosage; Penicillin Amidase; rekombinantní proteiny; Recombinant Proteins; kodon; transformace genetická; Codon; genetické vektory; Cloning, Molecular; průmyslová mikrobiologie; Transformation, Genetic; exprese genu; klonování DNA; penicilinamidasa; Bioreactors; promotorové oblasti (genetika); Promoter Regions, Genetic; Industrial Microbiology; genová dávka; Pichia; Genetic Vectors; Achromobacter; bioreaktory; Gene Expression